(3GdOahY GdTcdjI aj bGfhf CUhd GdeMGceGJ GdLRGFjI (B:s (3OQGSI ebGQfI (B/s - (3QYO, fHjd GdaGVds; (3QhHjQ, LGc gfQj,s 1940-; (3JGQg, aQfShG,s 1930- ((3HjQhJ (B:s (3GdehSSI GdMOjKI ddcJGH,s, 2020)
(3GdOahY GdTcdjI aj bGfhf CUhd GdeMGceGJ GdLRGFjI (B2009-2010(3, hgh OQGSI ebGQfI Hjf GdbGfhfjf GddHfGfj hGdaQfSj, jbY aj (B1240 (3UaMI hjbSe Edi LRCjf aj JbOjegeG ddcJGH CTGQ GdHQhaShQGf aj LGeYI HGfJjhf CSGS (B((3HGQjS(B) (3aQfShG JGQg hLGc(B-(3gfQj QhHjQ Edi Gf GdeDda Qei HUhQI QFjSI Edi eSGYOI QLGd GdbGfhf Ydi JaSjQ GdeGOI (B73 (3ef bGfhf CUhd GdeMGceGJ GdLRGFjI hJWHjbgG, hCfg jfHZj Cf jchf gPG GdcJGH HUhQI eSJeQI aj eJfGhd GdbVGI hGdeMGejf(B. (3HYOeG JfGhd GdeDda TQhW eeGQSI Mb GdEOdGA HGdOahY GdTcdjI, hPdc aj aUd JegjOj GfJbd Edi YQV MGdGJ gPg GdOahY hJMdjdgG (B((3GdaUd GdChd MJi GdaUd GdSGHY(B) (3djYQV ef Ke aj aUd KGef, WQb GdWYf HGdbQGQGJ GdaGUdI HgG(B: 1-(3GdaUd GdChd jNJU HGdOaY HGfJaGA GdUdGMjI JWQb GdeDda Edi GMJeGdjI GdOaY HGfJaGA UdGMjI GdeMGce GdhWfjI djfJbd Edi GdGNJUGU GdOGNdj ddeMGce GdLRGFjI, eHjfG eaghe GdUdGMjI GdfSHjI (B: (3GdGNJUGU GdfhYj, GdGNJUGU GdTNUj hGdGNJUGU GdecGfj, hdjJfGhd ef Ke GNJUGU GdeMGce GdGSJKfGFjI hGNJUGU GdeMGce GdLRGFjI GdYGOjI(B.s
(3jTJed Ydi cTGaGJ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdeMGceGJ GdLfGFjIs -- (3dHfGfs; (3bGfhf GdELQGAGJ GdLfGFjIs -- (3dHfGfs; (3GdOaGY Yf GdeJge (B((3ELQGAGJ LfGFjI(B)s -- (3dHfGfs